2019
DOI: 10.1186/s13568-019-0756-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inoculation by arbuscular mycorrhizal fungi on the composition of the essential oil, plant growth, and lipoxygenase activity of Piper aduncum L.

Abstract: The aim of this study was to evaluate the changes in the production of secondary metabolites Piper aduncum seedlings were inoculated by spores of the arbuscular mycorrhizal fungi (AMF) Rhizophagus clarus and Claroideoglomus etunicatum. P. aduncum seedlings were inoculated by spores of R. clarus and C. etunicatum and then, development parameters, root colonization, lipoxygenase (LOX) activity, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 35 publications
2
7
0
1
Order By: Relevance
“…At the same time, these relationships can regulate plant metabolism (such as antioxidant enzymes and peroxides) to alleviate drought damage to plants, thereby improving the tolerance of plants to drought stress. This phenomenon has been observed in C. camphora and C. bodinieri [15,16]. Furthermore, previous research has confirmed that C. migao can co-exist with some AM fungi [17].…”
Section: Introductionsupporting
confidence: 58%
“…At the same time, these relationships can regulate plant metabolism (such as antioxidant enzymes and peroxides) to alleviate drought damage to plants, thereby improving the tolerance of plants to drought stress. This phenomenon has been observed in C. camphora and C. bodinieri [15,16]. Furthermore, previous research has confirmed that C. migao can co-exist with some AM fungi [17].…”
Section: Introductionsupporting
confidence: 58%
“…Although it has been reported as the main component of P. pellucida EOs occurring in northern Brazil [1,7,9], plant colonization by E. asburiae and K. variicola did not affected its concentration. This probably happened because plant colonization by symbiotic microorganisms usually affects species rich in terpenes [14,21,38,90]. Similar effects have also been observed after herbivore attack [96][97][98].…”
Section: Plos Onementioning
confidence: 66%
“…asburiae which had a decrease in the concentration of ishwarane and an increase in 2,4,5-trimethoxystyrene ( Fig 4 ). The growth in the phenylpropanoid derivative content was an unexpected finding since monoterpene and sesquiterpene contents are usually the ones affected by microorganism inoculation [ 21 , 38 , 90 ]. The increase in this compound content may not have been reported for plant-microbe symbiosis, but 2,4,5-trimethoxystyrene could be involved in plant-defense since it has insecticidal activity [ 91 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Na Amazônia brasileira muitas espécies de PMA já foram estudadas, como Ontrichardia linifera Schott (Araceae), (Batista et al, 2019;Oliveira et al, 2019a;Silva et al, 2019a;Vilhena et al, 2019;Ferreira et al, 2020). Nas comunidades amazônicas, principalmente aquelas que se encontram localizadas distantes dos grandes centros médicos e de diagnósticos, esses vegetais constituem a fonte primária de recursos para cuidar da saúde ou curar de diversas afecções (Santos et al, 2019).…”
Section: Introductionunclassified